Faktor-Faktor Yang Berhubungan Dengan Dermatitis Kontak Akibat Kerja Pada Pekerja Cuci Mobil Di Bandar Lampung - Syukri, Muhammad; Sjahriani, Tessa; Kheru, Akhmad; Panonsih, Resati Nando (CV. Jasa Sukses Abadi, 2024)
Skin is the separator organ between the environmental parts of the body outside the body. Skin continuously is exposed to environmental factors in the form of physical, chemical, and biological. Therefore, if there is disease. This skin disease is caused by work (occupational dermatitis) namely a skin inflammation that results in a person’s activities. Contact dermatitis due to work is (DKAK) is skin inflammation that occurs due to the interaction between workers and the substance in the work environment. Objective: to find out the risk factors related to the occurrence of contact dermatitis due to work for car washing workers in Bandar Lampung. Method: The type of research used is analytic with cross sectional design. The sample in this study car washing workers in 5 sub-district area Rajabasa, Enggal, Labuhan Ratu, Way Halim, and Sukarame. Results: The distribution of frequency on the working shift in car washing workers who work more than 2 hours by 30 (75%) of workers, at a more contact order on 5x in a day 35 (87,5%) for workers, in the characteristics of chemicals that contain surfactant as much as 37 (92,5%) of workers, and get 22 (55%) of workers experience contact dermatitis due to work. Conclusion: There is a significant relationship between working shift with dkak with the results of the chi-square test 0,001, there is a significant relationship in the speed condition with dkak with the results of the chi-square 0,008. And there is a significance relationship between the chemical charateristics with the results of the chi-square test 0,046.